Mechanical Pulp from Eucalyptus tereticornis - Guha, S. R. D.; Mukherjea, V. N.; Madan, R. N. (Indian Forester, 1962)
Laboratory experiments on the production of mechanical pulp from Eucalypltus tereticornis are described. Standard pulp sheets were made from a mixture of 60 per cent mechanical pulp from this species and 40 per cent imported bleached sulphate wood pulp. Strength properties of standard sheets prepared from mechanical pulp produced under suitable conditions are satisfactory for the production of newsprint but the colour is poor and cannot be easily bleached.